Pengembangan Sistem Dispensasi Kendaraan Keluar Kampus (Studi Kasus Di Universitas Brawijaya) - Aulia Rahman; Ismiarta Aknuranda; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Scenario parking system that exist in Brawijaya University is when vehicle will come out of parking area hence parking gate will do checking by asking letter of vehicle number (STNK). Sometimes vehicle owners forget to take vehicle registration. Brawijaya University authority provides ease by giving out campus dispensation letter as a substitute for vehicle registration obtained from Command Headquarter of Brawijaya University. There are some disadvantages of using the manual system which is the inaccurate verification of the dispenser in the Command Headquarters to ensure the applicant is the owner of a valid vehicle or not. In addition, the campus residents can entrust the goods in the campus area to the officers of the security guard. The Security Guard at Brawijaya University's Command Headquarters followed up with the announcement of the findings of lost items through social media. In fact publication of lost items through social media is less effective. From both of these problems the authors provide solutions by developing the system dispensasi vehicle out campus web based. These system requirements are derived from the requirements analysis results. In designing this system contains sequence diagrams, class diagrams, data base design and interface design. In the implementation of this system using Codeigniter framework and tailored to the design of the system created. From the results of validation and compatibility testing, indicating that this system has been running in accordance with the requirements specified.